THE INFLUENCE OF GOVERNMENT POLICIES, TRADE UNIONS AND MANAGERIAL ROLES ON THE STABILITY OF INDUSTRIAL RELATIONS WHICH IMPACT THE PERFORMANCE OF TIN MINING SMELTER COMPANIES IN THE PROVINCE OF BANGKA BELITUNG ISLANDS - Susanto, Ady; Sugianto, Efendi; Hamdan, Hamdan; Juhari, Juhari (PT. Hafasy Dwi Nawasena, 2025)
This study aims to examine the influence of government policies, trade unions, and managerial roles on the stability of industrial relations and their impact on the performance of tin mining smelter companies in the Bangka Belitung Islands Province. The main problem in this study is how the interaction of these three independent variables can create a stable, productive, and sustainable working relationship climate, which in turn affects the company's overall performance. The method used in this study uses a quantitative approach with a descriptive-causal design, where data is collected through a questionnaire of 170 respondents, consisting of tin smelter employees and employees of the Manpower Office. The instrument was measured on a five-point Likert scale and analyzed using multiple linear regression and simple linear regression to determine the correlative relationship between the variables studied. Based on the results of the study, it can be concluded that simultaneously government policies, trade unions, and managerial roles have a significant influence on the stability of industrial relations. Partially, each independent variable also makes a significant contribution to the stability of industrial relations. This research makes a theoretical contribution to the study of industrial relations and offers practical recommendations for policymakers, company management, and trade unions to strive for a positive and sustainable work environment.